A higher-order equation for modeling strand bond in pretensioned concrete beams. (15th January 2017) - Ramirez-Garcia, Alberto T.; Dang, Canh N.; Micah Hale, W.; Martí-Vargas, J.R.
Highlights: A model was developed using the Thick-Walled Cylinder theory to predict bond behavior in the transfer zone. The model determined the stress distribution, degree of cracking, and transfer length. A data set from the literature and from beams cast for the study was used to validate the model. The proposed model predicted transfer lengths that ranged from 90 to 121% of the measured values. Abstract: In pretensioned concrete members, the bond between prestressing strands and concrete in the transfer zone is necessary to ensure the two materials can work as a composite material. This study develops a computer program based on the Thick-Walled Cylinder theory to predict the bond behavior within the transfer zone. The bond was modeled as the shearing stress acting at the strand-concrete interface, and this generated a normal stress to the surrounding concrete. The stresses developed in the concrete often exceeded its tensile strength, which resulted in radial cracks at the strand-concrete interface. These cracks reduced the concrete stiffness and redistributed the bond strength along the transfer zone. The developed program was able to determine the bond stress distribution, degree of cracking, and transfer length of the prestressing strands. The program was validated using a data set of transfer lengths measured at the University of Arkansas and a data set collected from the literature.